N-Halosuccinimide enables cascade oxidative trifluorination and halogenative cyclization of tryptamine-derived isocyanides - Jun-Yunzi Wu; Long-Ling Huang; Jia-Luo Fu; Jia-Yi Li; Shuang Lin; Shuang Yang; Zhi-Shu Huang; Honggen Wang; Qingjiang Li (Nature Communications)
Abstract Both the pyrroloindoline core and N–CF3 moiety hold significant importance in medicinal chemistry. However, to date, no instances of constructing N–CF3-containing pyrroloindolines have been reported. Herein, we present a robust and operationally simple approach to assembling such intriguing skeletons from tryptamine-derived isocyanides through a cascade sequence, which includes an oxidative trifluorination and a subsequent halogenative cyclization. Key to the success lies in the development of a facile conversion of isocyanides to N–CF3 moiety with commercially available reagents N-halosuccinimide and Et3N·HF. The protocol features mild reaction conditions, broad functional group tolerance, good to excellent yields, and high diastereoselectivities. In addition, we demonstrate that the halide substituent within the products serves as a versatile functional handle for accessing diverse C3-quaternary-substituted N–CF3-pyrroloindolines.